007 The MS-STAT2 trial in secondary progressive MS – study design and update. Issue 6 (27th May 2022) - Williams, Thomas; John, Nevin; Calvi, Alberto; Doshi, Anisha; Bianchi, Alessia; Brownlee, Wallace; Blackstone, James; Braisher, Marie; Anglias, Floriana De; Chataway, Jeremy
Abstract : The MS-STAT2 study is a Phase III, 3 year multi-centre, randomised, placebo-controlled trial assessing the efficacy of 80mg simvastatin vs. placebo in secondary progressive multiple sclerosis (SPMS). Building upon the promising results of the MS-STAT1 study, it is an academically led study funded through a collaboration of the NIHR HTA, MS Society (UK), National MS Society (US), and the Rosetrees Trust. Here we will provide an update on the trial design and progress, including: The agreed trial extension period Adaptations to recruitment targets and trial design An update on trial sites where patients can be referred An update on current trial progress thomas.williams@nhs.net